Beat to beat: device for treatment adherence in hypertension (2018)
This report discusses the importance to address the low care of patients suffering from hypertension since it is asymptomatic. We go through an observation process involving patients and medical experts, and identify different needs, concluding that a way to control their disease neglection is by a design that makes them take their mediations in the right times and that can alert family and/or caretakers if they are not following the treatment. Furthermore, it would be a way for the doctor and pharmacist to monitor the medication taking of the patient. Our target with this are mainly male hypertension patients of around 50-55 years of age, that develop in an urban middle-class environment